2016
DOI: 10.1177/1687814016676943
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sub-shift control algorithm for an agricultural tractor with hydro-mechanical transmission

Abstract: A sub-shift control algorithm was proposed for an agricultural tractor with hydro-mechanical transmission. The hydromechanical transmission investigated in this study consists of a hydro-static unit and planetary gear sets which provide a continuously variable transmission function and four sub-shift gears. The sub-shift needs to be carried out at the hydrostatic unit stroke where the speed of the off-going and oncoming clutches is synchronized. To reduce the hydro-static unit stroke error due to the nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The results showed that the average steady state error can be controlled within ±0.0125% and the stability of the system has improved. Ahn [16] developed a sub-shift algorithm for a tractor equipped with hydro-mechanical transmission. It was found experimentally that there was smooth performance during the sub-shift without torque interruption and shock.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the average steady state error can be controlled within ±0.0125% and the stability of the system has improved. Ahn [16] developed a sub-shift algorithm for a tractor equipped with hydro-mechanical transmission. It was found experimentally that there was smooth performance during the sub-shift without torque interruption and shock.…”
Section: Introductionmentioning
confidence: 99%